Cognitive requirement of accounting tasks : a task analysis in Chinese vocational school textbooks - Zhou, Yijun [Verfasser] (wbv Media GmbH & Co. KG, 2022)
"Competence orientation has become a defining element of vocational education in German-speaking countries. In this context, tasks are considered the 'transmission belts' to implement the reformed educational standards. In her dissertation the author takes a view on the systematic analysis of task characteristics as a method to inspect the degree of tasks' cognitive requirements. The theoretical-conceptual part of the dissertation gives a psychological and didactical justification of the principles underlying the tasks' cognitive requirement. The effects are analysed in two empirical studies. The first study takes a look on the basis of accounting tasks from Chinese vocational school textbooks, using the structuring content analysis (Mayring, 2008). The second empirical study inspects accounting teachers' perceptions and judgments by interviews. Based on the results, the author develops suggestions for the use of the concept of tasks' cognitive requirement in the didactic training of (prospective) teachers at commercial schools." (Publisher, BIBB-Doku)
Keywords: S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; L 4.1.1 Klassische Lehr-Lernmedien; P 3.2 Lehrpersonal; 370; Berufsschule; Schulbuch; Schulbuchforschung; Aufgabe; Kognitive Fähigkeit; Lehrer; Lehrerbildung; Didaktik; China